Ten year public health impact of 13-valent pneumococcal conjugate vaccination in infants: A modelling analysis. Issue 45 (21st October 2020) - Chapman, Ruth; Sutton, Kelly; Dillon-Murphy, Desmond; Patel, Shreeya; Hilton, Betsy; Farkouh, Ray; Wasserman, Matt
Highlights: Pneumococcal disease is a substantial contributor to disease in children globally. The introduction of pneumococcal conjugate vaccines has reduced this burden. We estimate that PCV13 has prevented over 175m cases of disease and 624, 000 deaths. These results are conservative, given focus on direct effect and exclusion of broader benefits. While results are substantial, higher valent PCVs will help combat emerging serotypes. Abstract: Pneumococcal disease is a substantial contributor to illness and death in young children globally. The introduction of 7-valent pneumococcal conjugate vaccine (PCV7) in 2000 had a significant impact in preventing pneumococcal disease in both vaccinated children and unvaccinated individuals (through herd effect). A higher valent PCV13 replaced PCV7 in late 2009. This analysis was undertaken to assess how many cases and deaths have been averted over the last decade since PCV13 introduction. A model estimated the number of infants vaccinated annually with PCV13, as well as the number of cases and deaths of invasive pneumococcal disease, pneumococcal pneumonia, and acute otitis media cases averted. PCV13 vaccination was estimated to have prevented 175.2 million cases of all pneumococcal diseases and 624, 904 deaths globally between 2010 and 2019. These results demonstrate the substantial public health impact of PCV13 and highlight the importance of increasing the global reach of PCV programs.